Gestão de portfólio ágil no contexto de desenvolvimento de sistemas digitais: estudo de caso múltiplo em empresas brasileiras - Góes, Roberto de Souza (2024)
In the IT departments of companies, especially in their software development processes, there is currently a strong emphasis on the use of agile practices. The concepts embedded in agile methods demand cultural changes aimed at responding to frequent market changes, as well as improving speed and innovation in serving customers. However, the success factors applicable to projects do not lead to efficiency at the portfolio level, as structural changes are more complex. In response, the market has seen the emergence of new agile models that operate at the project portfolio level, which are not suitable for every type of company, and the adaptations made for their use are not always the most appropriate. In this context, the aim of this study is to evaluate how large Brazilian companies use Agile Project Portfolio Management within the context of digital systems development. To this end, a bibliometric study was conducted, followed by a systematic literature review to formulate the interview guide and identify the topics of interest to be addressed in a field research study, through the application of a multiple case study. The results found can serve as a reference guide for best practices in Agile Portfolio Management, based on the patterns identified in the case studies, which may support Brazilian companies in leveraging and applying agile practices at this level of project management.